Are Checking Accounts in American Banks Permissible Under Islamic Laws? A Note (American Journal of Islam and Society, 1985)
The purpose of this note is to stimulate the thought of Muslim scholarsabout a neglected aspect of American banking business. namely thepayment of interest on demand deposits (checking accounts).Demand deposits represent funds that commercial banks use toextend loans to the public and purchase interest-bearing securities. Therevenues from these activities are a major source of income forcommercial banks. Consequently, fierce competition exists amongbanks to attract such funds: However, competition for these fonds. untilrecently, could not take the form of an explicit interest rate because theAmerican banking laws prohibit the payments of explicit interest rateson demand deposits .. Existing laws have relaxed this prohibition forsome forms of demand deposits (e.g. Negotiable Orders of WitndrawalsNOW accounts), though the prohibition still holds in the case of what iscommonly called in the banking jargon regular checking accounts, i.e ..checking accounts that do not explicitly yield interest to the holders.Because of the intensity of competition among commercial banks toattract public deposits. and  in the presense of the legal prohibitionagainst explicit interest payments on regular checking accounts bankshave devised alternative outlets to compete for the checking accountsfunds. Perhaps the most obvious alternative is for a bank to reduce (orremit) charges to depositors for the use of bank payments services belowthe cost to the bank of providing those services. Others take the form offor example, providing a wide range of cash management services atvery nominal fees and occasional gifts. In economic literature these arecalled implicit interest rates, and many recent empirical studies haveestablished the fact that commercial hanks in the U.S. do in fact pay highimplicit interest rates on non-interest bearing demand deposits ofapproximately equal value to the rate which would be explicitly paid inthe abscence of the legal prohibition ...